Nontraditional vegetable crops and food security among smallholder farmers in Guatemala - von Braun, Joachim; Immink, Maarten D. C. (International Food Policy Research Institute, 1994)
Export-oriented agricultural production has a log tradition in Guatemala that has resulted in a highly dualistic agricultural sector. Traditional exports, which include coffee, cotton, sugar, bananas, and beef, accounted for approximately 70 percent of total agricultural exports in the late 1980s. Most of the economic gains from agricultural development have been confined to the large-scale modern sector. Increasing concerns are being expressed about the food security of the low-income rural and urban populations.